Implementasi Pembuatan Sumur Resapan Air Untuk Penanggulangan Banjir Di Kota Pekanbaru Berdasarkan Peraturan Daerah Nomor 10 Tahun 2006 Tentang Sumber Daya Air Dan Sumur Resapan - Hendri, Hendri; Ardiansah, Ardiansah; fahmi, sudi (Institut Pemerintahan Dalam Negeri (IPDN) Kampus Sumatera Barat, 2024)
Regional Regulation Number 10 of 2006 contains policies regarding the obligation to build infiltration wells, it is clearly regulated that the obligation to construct infiltration wells is addressed to every person in charge. Responsible for the construction covering the ground surface and the number of infiltration wells made in accordance with the total land surface covered by the building. This rule is contained in Article 19 paragraph (4) of Regional Regulation Number 10 of 2006 which reads: